2021
DOI: 10.1039/d0mh01540g
|View full text |Cite
|
Sign up to set email alerts
|

Patterning and control of the nanostructure in plasma thin films with acoustic waves: mechanicalvs.electrical polarization effects

Abstract: Plasma thin film deposition assisted with acoustic waves renders a patterned structure due to sheath ions local bombardment effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…We have recently shown that the excitation configuration proposed in Scheme 1 and Figures S1 and S2 (Supporting Information), consisting of two planar electrodes on LiNbO 3 plates subjected to rf signaling at ≈3.5 MHz, generates patterns of acoustic standing waves [34] with a submillimeter wavelength. Since the de-icing and active anti-icing processes studied in this work can be quite dependent on the AW characteristics, the generated standing AWs have been simulated using the procedure described in the experimental and method section.…”
Section: Simulation Of Awsmentioning
confidence: 99%
“…We have recently shown that the excitation configuration proposed in Scheme 1 and Figures S1 and S2 (Supporting Information), consisting of two planar electrodes on LiNbO 3 plates subjected to rf signaling at ≈3.5 MHz, generates patterns of acoustic standing waves [34] with a submillimeter wavelength. Since the de-icing and active anti-icing processes studied in this work can be quite dependent on the AW characteristics, the generated standing AWs have been simulated using the procedure described in the experimental and method section.…”
Section: Simulation Of Awsmentioning
confidence: 99%
“…Assisting the plasma deposition of the nano-matrixes with acoustic waves leads to patterning phenomena characterized by substantial lateral changes in nanostructure, thickness and properties [17]. In addition, changes in crystal structure are also induced.…”
Section: Concept Of Vibration-assisted Activation the Pulse-plasma De...mentioning
confidence: 99%
“…Changing the acoustic driving frequency can be employed to modify the pattern size. The piezoelectric elements and layers are also capable of generating electromagnetic radiation [17]. Acoustic and electromagnetic holograms with specified frequency and spatial characteristics are capable of providing spatial marking of the structure of the grown carbyne-enriched nanostructures.…”
Section: Concept Of Vibration-assisted Activation the Pulse-plasma De...mentioning
confidence: 99%
“…Assisting the nanomaterial growth through generating the Rayleigh-type SAW leads to patterning phenomena characterized by substantial lateral changes in the nanostructures, thicknesses and properties [ 44 ]. Certain frequencies of acoustic vibrations are capable of forming various geometric shapes.…”
Section: Vibration-assisted Activation Of the Pulse-plasma Growth Zonementioning
confidence: 99%
“…The piezoelectric elements and layers are also capable of generating electromagnetic emissions [ 44 ]. Acoustic and electromagnetic holograms with specified frequencies and spatial characteristics are capable of providing the spatial markings of the structure of the grown 2D-ordered linear-chain carbon-based nanomatrix.…”
Section: Vibration-assisted Activation Of the Pulse-plasma Growth Zonementioning
confidence: 99%